On the etiology of incident brain lacunes: longitudinal observations from the LADIS study - Gouw, Alida A.; Flier, Wiesje M. van der; Pantoni, Leonardo; Inzitari, Domenico; Erkinjuntti, Timo; Wahlund, Lars O.; Waldemar, Gunhild; Schmidt, Reinhold; Fazekas, Franz; Scheltens, Philip; Barkhof, Frederik; Hennerici, Michael G.; et al. (Stroke, 2008)
Background and Purpose— We investigated regional differences in MRI characteristics and risk factor profiles of incident lacunes over a 3-year period.Methods— Baseline and 3-year follow-up MRI were collected within the LADIS study (n=358). Incident lacunes were characterized with respect to brain region, their appearance within pre-existent white matter hyperintensities (WMH), surrounding WMH size, and risk factors.Results— 106 incident lacunes were observed in 62 patients (58 subcortical white matter [WM], 35 basal ganglia, and 13 infratentorial). Incident subcortical WM lacunes occurred more often within preexisting WMH (P=0.01) and were mostly accompanied by new and expanded WMH (P<0.001), compared to incident basal ganglia and infratentorial lacunes. Risk factors for incident subcortical WM lacunes were history of hypertension and stroke, whereas atrial fibrillation predicted incident basal ganglia/infratentorial lacunes.Conclusion— Differences in relation to WMH and risk factor profiles may suggest that incident lacunes in the subcortical WM have a different pathogenesis than those in the basal ganglia and infratentorial region.